Analysis of Influencing Factors of the Use of E-Comic on Learning Platforms Digital Using Technology Acceptance Model (TAM) - Jumiati; Naufal Fidha Sulaeman; Pooveneswaran Nadajaran (LEOTECH: Journal of Learning Education and Technology, 2026)
This study examines factors influencing the acceptance of e-comic use on digital learning platforms using an extended Technology Acceptance Model (TAM). A quantitative survey was conducted involving 118 elementary school students, and the data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The results indicate that perceived usefulness significantly influences attitude and behavioral intention to use e-comics. Perceived ease of use does not directly affect attitude or behavioral intention but significantly influences perceived usefulness. Accessibility and student support also play important roles in increasing technology acceptance. The structural model explains 52.2% of the variance in behavioral intention (R² = 0.522), indicating moderate explanatory power. These findings strengthen the application of TAM in the context of digital learning media and highlight the importance of perceived usefulness, accessibility, and system support in supporting the adoption of e-comics in primary education.